Adrenal disease in childhood : clinical and molecular aspects - Hughes, I. A; Clark, Adrian J. L (Karger, 2000)
Adrenal disease in children poses an immensely difficult diagnostic and management problem for the paediatrician in view of the large number of rare pathologies that may present in this way. This volume brings together the expertise of the acknowledged leaders in specific adrenal disorders to provide a readily accessible text that combines a detailed description of the molecular origins of these diseases, as they are currently understood, with a unique account of the clinical features and therapeutic options. Beginning with disorders that primarily affect adrenal development and progressing towards the defects that interfere with steroid production, the reader gains considerable insight into the normal physiology of the adrenal cortex particularly as revealed by clinical disorders. The major contributions of modern biochemistry and molecular genetics in our current understanding are visible throughout, providing a unique overview of adrenocortical biology.
Endocrine development ; vol. 2
Keywords: nemoci nadledvin; Adrenal Gland Diseases; endokrinologie